A micro-crack initiation life simulation method by improving the Tanaka-Mura's model of slip behavior. (April 2021) - Liu, Xiaotao; Lu, Shan
Highlights: Micro-crack initiation considering varied slip irreversibility and hardening. A slip irreversibility quantification model to load and microstructure are proposed. Simulation examples in FCC material and comparison with the related experiment. Discussion about how the slip behavior affect micro-crack initiation life. Abstract: A micro-crack initiation simulation model was proposed with varied slip irreversibility and slip hardening (VSISH), by improving the Tanaka-Mura's model. A power law to relate the slip irreversibility parameter to the load and the microstructure information was proposed. The shear strain range in Tanaka-Mura's model was re-derived for introducing slip hardening behavior. Several microstructure examples in three-dimensions were given and the evaluated mean fatigue life has a minimum error less than 3.3% compared with the experimental data. It was demonstrated that the constant-slip-irreversibility strategy and an existing irreversibility model were specific cases of our model.